2002
DOI: 10.1111/j.1348-0421.2002.tb02769.x
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbial Diversity in a Strict Vegetarian as Determined by Molecular Analysis and Cultivation

Abstract: Fecal microbial diversity in a strictly vegetarian woman was determined by the 16S rDNA library method, terminal restriction fragment length polymorphism (T‐RFLP) analysis and a culture‐based method. The 16S rDNA library was generated from extracted fecal DNA, using bacteria‐specific primers. Randomly selected clones were partially sequenced. T‐RFLP analysis was performed using amplified 16S rDNA. The lengths of T‐RF were analyzed after digestion by HhaI and MspI. The cultivated bacterial isolates were used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
97
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(107 citation statements)
references
References 37 publications
8
97
1
1
Order By: Relevance
“…There was a similar observation of the mirobiota in human vegetarian feces, which showed 90.7% of Fermicutes, 59.6% of Clostridium rRNA Subcluster XIVa, and 6.0% of CytophagaFlexibacter-Bacteroides (Hayashi et al, 2002b). However, no bacterial species contributing to the fiber degradation in the proximal colon was identified in this study, suggesting that the fiber-degrading bacteria, such as Ruminococcus albus, Ruminococcus flavefaciens, and Fibrobacter succinogenes, may be a minor species, at least less than detection levels.…”
Section: Discussionsupporting
confidence: 49%
“…There was a similar observation of the mirobiota in human vegetarian feces, which showed 90.7% of Fermicutes, 59.6% of Clostridium rRNA Subcluster XIVa, and 6.0% of CytophagaFlexibacter-Bacteroides (Hayashi et al, 2002b). However, no bacterial species contributing to the fiber degradation in the proximal colon was identified in this study, suggesting that the fiber-degrading bacteria, such as Ruminococcus albus, Ruminococcus flavefaciens, and Fibrobacter succinogenes, may be a minor species, at least less than detection levels.…”
Section: Discussionsupporting
confidence: 49%
“…The non exhaustive data of the microbiota we found show species only from Clostridiales order, Clostridiaceae, Eubacterium and Lachnospiraceae family. This is not surprising since novel or yet uncultured species are most often identified upon characterization of fecal microbiota using cloned 16S rDNA genes librairies [11]. Recent culture-independent studies have shown that approximately 70% of the dominant human gut microorganisms have not been isolated and described [3].…”
Section: Discussionmentioning
confidence: 99%
“…Each previously uncharacterized phylotype was identified only in a single subject, consistent with the observed low level of interpersonal consensus. That 7.1% of clones and 17.8% of phylotypes were previously uncharacterized, based on a criterion of Ͻ97% similarity, is much lower than in other human niches, including the intestine (23), feces (39), tongue dorsum (40), and human subgingival crevice (20). The presence of a few dominant species in the skin, use of varying definitions in different studies (19,23,41), as well as the progressive recognition of human-associated species, may partially explain this difference.…”
Section: Discussionmentioning
confidence: 99%